Harmonization of international standards and the national legal system regarding the institutional development of civil society entities - Bohiv, Yaryna (Global Prosperity, 2023)
The article analyzes the impact of international standards that contribute to the construction of civil society in Ukraine, defines the spheres of their interaction, as well as the mechanisms of its harmonization with the national legal system. The international standards of the functioning of civil society institutions, in particular, the standards of the Council of Europe, were studied, as well as the state of implementation of such provisions in the legal system of Ukraine was analyzed. The provisions of the Recommendation of the Committee of Ministers of the Council of Europe (regarding the creation and operation of non-governmental organizations) dated October 10, 2007, as well as the Fundamental Principles regarding the status of non-governmental organizations in Europe dated July 5, 2002, were analyzed. The compliance of the provisions of the Law of Ukraine «On Public Associations» with European standards in the field of legal regulation of non-governmental organizations was investigated. It has been established that the harmonization of international standards and the national legal system regarding the institutional development of civil society entities is a rather broad and variable category. Based on specific examples of the development of relations between international institutions and civil society, it was established that the efforts of foreign partners can be directed at the political environment of the state and its modification; economic and financial system of the country; social environment and development of specialized civic institutions; provision of educational and informational services, etc. After analyzing a significant number of scientific studies, the issue of the institutionality of political organizations and their regulation at the international level, as well as the financial mechanisms of the development of civil society institutions in our country, was found to be insufficiently resolved.